2010
DOI: 10.1165/rcmb.2009-0254oc
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of IRF7 in Nasal Epithelial Cells from Smokers after Infection with Influenza

Abstract: Smokers are more susceptible to respiratory viral infections, including influenza virus, but the mechanisms mediating this effect are unknown. To determine how epithelial cells contribute to the enhanced susceptibility seen in smokers, we established an in vitro model of differentiated nasal epithelial cells (NECs) from smokers, which showed enhanced mucin expression. The NECs from smokers responded to influenza infection with greater cytotoxicity, release of interleukin-6, and viral shedding than NECs from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 42 publications
(54 reference statements)
7
74
0
Order By: Relevance
“…However, because of ethical considerations, there are limited clinical studies investigating the mechanisms involved; animal research (e.g., mouse, guinea pig, rat) has been proven advantageous in the exploration of the mechanisms involved in CSinduced COPD (15). In addition, recent studies (14,61,82) have demonstrated that CS can impair the antiviral host defense. For instance, type I IFN, a key mediator involved in antimicrobial signaling pathways, is attenuated after cigarette smoke exposure.…”
Section: Effects Of Cs In Animal Modelsmentioning
confidence: 99%
“…However, because of ethical considerations, there are limited clinical studies investigating the mechanisms involved; animal research (e.g., mouse, guinea pig, rat) has been proven advantageous in the exploration of the mechanisms involved in CSinduced COPD (15). In addition, recent studies (14,61,82) have demonstrated that CS can impair the antiviral host defense. For instance, type I IFN, a key mediator involved in antimicrobial signaling pathways, is attenuated after cigarette smoke exposure.…”
Section: Effects Of Cs In Animal Modelsmentioning
confidence: 99%
“…Smoking not only induces cellular damage and inflammation but also serves as an immunosuppressor (37). Although the underlying molecular mechanisms of smoking-induced disease remain largely unknown, one of the proposed mechanisms involves epigenetic modifications (e.g., DNA methylation) that potentially alter gene expression profiles of CS-exposed target cells (15,19,22,39). Genespecific epigenetic regulation can occur through loss or gain of cytosine methylation in promoter-associated cytosine-phosphate-guanine (CpG) islands (33).…”
mentioning
confidence: 99%
“…For example, virus-induced cytokine and chemokine expression is modified in CS-exposed epithelial cells (30). We and others have previously demonstrated that CS exposure significantly alters interferon-dependent antiviral responses at the level of the epithelium (19,40). Exposure to CS also alters the ability of epithelial cells to communicate with resident immune cells, such as dendritic cells and Natural Killer (NK) cells in the context of viral infections (17,18).…”
mentioning
confidence: 99%
“…Transcriptional profiling of AMs in smokers has indicated a marked macrophage reprogramming in smokers (3,4), with suppression of inflammatory genes associated with classical M1-related inflammatory/immune genes and induction of genes associated with various M2-polarization programs relevant to tissue remodeling and immunoregulation, findings that are consistent with reduced innate immune responses and increased susceptibility to respiratory infections in smokers or CS-exposed individuals (2,5). Actions of CS on airway epithelial cells affect their production of inflammatory or host defense mediators (6)(7)(8)(9) and their interactions with DCs (10,11). Furthermore, direct actions of CS on DCs may affect DC maturation (12) and polarize T helper (Th) 2 immune responses (13,14).…”
mentioning
confidence: 99%